2013
DOI: 10.3390/molecules18033445
|View full text |Cite
|
Sign up to set email alerts
|

Article Synthesis and Trypanocidal Activity of Novel 2,4,5-Triaryl-N-Hydroxylimidazole Derivatives

Abstract: Herein, we report the design, synthesis and trypanocidal activity of some novel trisubstituted imidazole derivatives. These heterocyclic derivatives were structurally planned by exploring the concept of molecular hybridisation between two arylhydrazones derived from megazol, which has potent trypanocidal activity. The trypanocidal activity of these triarylimidazole derivatives was evaluated against infective trypomastigote forms of OPEN ACCESSMolecules 2013, 18 3446T. cruzi and the derivative 2'-(4-bromophenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…For example, it has been shown that 1-hydroxyimidazole derivatives display insecticidal and herbicidal properties, 2 exhibit antiprotozoal activity. 3,4 It is supposed that 1-hydroxyimidazoles exist in either Nhydroxy or N-oxide tautomeric form. Scheme 1.…”
Section: Graphical Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that 1-hydroxyimidazole derivatives display insecticidal and herbicidal properties, 2 exhibit antiprotozoal activity. 3,4 It is supposed that 1-hydroxyimidazoles exist in either Nhydroxy or N-oxide tautomeric form. Scheme 1.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…One of the most widespread and convenient methods to synthesize 1-hydroxyimidazoles is a cyclization of starting aldehydes with α-hydroxyiminoketones and ammonium acetate 1,2,4,7,23,24,[26][27][28][29][30] in alcohols or glacial acetic acid. Scheme 2.…”
Section: Synthesis Of Compoundsmentioning
confidence: 99%
“…Structures of thiochroman-4-ones ( [1][2][3][4][5] and hydrazone derivatives (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). …”
Section: Methodsmentioning
confidence: 99%
“…In addition, numerous hydrazones have been reported to possess interesting biological activities such as antitumoral, antiviral and antiparasitic effects [8][9][10]; some hydrazones also exhibit activity against the parasites that cause malaria, leishmaniasis and Chagas disease [3,[11][12][13][14][15][16][17][18], where the inhibition of proteases and represent the most common mechanism of action for the hydrazones [16,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These 1-hydroxyimidazoles/imidazole N-oxides are among a number of active drugs known to exist in tautomeric forms, at least in solution [7]. Among the therapeutic activities of 1-hydroxyimidazole/imidazole N-oxide compounds are herbicidal [8,9], fungicidal and bacteriosidal [10], antihypertensive [11], antiviral [12] and typanocidal activities [13,14].…”
Section: Introductionmentioning
confidence: 99%